Immunohistochemical Staining on an Excision Biopsy Specimen as a Diagnostic Modality for Rare Idiopathic Hepatocellular Adenoma: A Case Report - Juferdy Kurniawan; Andri Sanityoso; Toar JM Lalisang; Ening Krisnuhoni; Sahat Matondang; Abirianty P Araminta; Lutfie Lutfie (Acta Medica Indonesiana)
Hepatocellular adenoma is an extremely rare benign tumor of the liver which predominantly in young women. Its rare incidence with estimated 3-4 cases per 1.000.000 annually makes it a diagnostic challenge. Here we present a 30-year-old female patient with hepatocellular adenoma without classic risk factors. A series of work up tools have been performed in order to diagnose the condition. None but excision biopsy from segmental resection had been showed to increase diagnostic confidence. This case illustrates the role of immunohistochemical staining from excision biopsy as the best diagnostic modality of hepatocellular adenoma as well as therapeutic modality to prevent malignant transformation.